2018
DOI: 10.1080/03610918.2017.1387663
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian adaptive lasso with variational Bayes for variable selection in high-dimensional generalized linear mixed models

Abstract: This article describes a full Bayesian treatment for simultaneous fixed-effect selection and parameter estimation in high-dimensional generalized linear mixed models. The approach consists of using a Bayesian adaptive Lasso penalty for signal-level adaptive shrinkage and a fast Variational Bayes scheme for estimating the posterior mode of the coefficients. The proposed approach offers several advantages over the existing methods, for example, the adaptive shrinkage parameters are automatically incorporated, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Using the Bayesian adaptive lasso (BaLasso) prior proposed by [45] it is also possible to extend our individual fixed-effects selection approach to account for (ordered) group selection by imposing different shrinkage levels to different coefficients. A variational Bayes approach for generalized linear models with priors of this type has been explored by [81], where the variational parameter updates of their VBGLMM algorithm could be streamlined using the framework studied in our work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Bayesian adaptive lasso (BaLasso) prior proposed by [45] it is also possible to extend our individual fixed-effects selection approach to account for (ordered) group selection by imposing different shrinkage levels to different coefficients. A variational Bayes approach for generalized linear models with priors of this type has been explored by [81], where the variational parameter updates of their VBGLMM algorithm could be streamlined using the framework studied in our work.…”
Section: Discussionmentioning
confidence: 99%
“…[1] propose a sparse variational Bayes analysis of linear mixed models which focuses on random effects shrinkage via decomposition of the random effects vector covariance matrix. A more recent contribution is [81], where the suggested approach performs simultaneous fixed-effect selection and parameter estimation via variational Bayes and Bayesian adaptive lasso. However, the approach is limited to high-dimensional two-level generalized linear mixed models and does not account for any streamlined updating improvements.…”
Section: Contribution and Article Organizationmentioning
confidence: 99%
“…The penalization in model ( 2) is a particular case of the Bayesian lasso of Park and Casella (2008) that makes use of a Gamma prior on the Laplace squared scale parameter. Tung et al (2019) show the use of MFVB for variable selection in generalized linear mixed models via Bayesian adaptive Lasso. Ormerod et al (2017) develop a MFVB approximation to a linear model with a spike-and-slab prior on the regression coefficients.…”
Section: Alternative Response and Penalization Distributionsmentioning
confidence: 99%
“…Armagan & Dunson (2011) propose a sparse variational Bayes analysis of linear mixed models which focuses on random effects shrinkage via decomposition of the random effects vector covariance matrix. A more recent contribution is Tung et al (2019), where the suggested approach performs simultaneous fixed-effect selection and parameter estimation via variational Bayes and Bayesian adaptive lasso. However, the approach is limited to high-dimensional two-level generalized linear mixed models and does not account for any streamlined updating improvements.…”
Section: Contribution and Article Organizationmentioning
confidence: 99%